The Future Strategies of the Wind Power Development in Albania: Case Study: “Qafe Thane,” Pogradec, Albania - Malka, Lorenc; Bebi, Elena; Alcani, Majlinda; Konomi, Ilirian; Bartocci, Pietro; Berberi, Evis; Shehu(Tola), Matilda; Gjeta, Ardit; Rrapaj, Ermonela (International Journal of Energy Economics and Policy, 2021)
The development of the electricity sector in Albania continues to be fenced by high rates of inefficiencies, insufficient security of supply, low rate of RES investment including wind power plants and the need to further unbundle and liberalise the energy market following the adoption of the legal basis, including GHG credits is inevitable. A lot of issues are set to face the challenges of energy transition, oriented by the Albanian government's endeavor to maintain a sustainable, secure, flexible in time, efficiently supplied, climate-friendly and affordable energy supply system is required. The most critical aspects to attain 2030 energy goals and beyond cannot be achieved without the promotion of carbonless power technologies reducing (GHG) emissions. As a consequence, huge investments in RES energy based power generation systems and related RES technologies are required. To subjugate the barriers to clean energy technology implementation especially at the preliminary feasibility stage, the latest model, RETScreen Expert 8 added the ability to rapidly analyze the feasibility of multiple wind power plant options at real site condition. This fast feature of the model enables us to assess the real potential of the proposed 27 MW wind farm by choosing a set of 16 different turbine types and models combined into 14 possible scenarios with the aim to expand the capacity in the future is applied. From the simulation executed in RETScreen Expert the technical and economic optimization of the proposed energy system is achieved. Sector-specific actions are explored in the paper, but at the higher level of specific investment costs and a number of cross-cutting actions that should be addressed with urgency from policy makers in the country are identified. Keywords: Wind Power Plant, HPP, RETScreen Expert, Net Present Value, Internal Rate of Return, Cash Flow JEL Classifications: Q4, Q42, Q47, Q48, Q58 DOI: https://doi.org/10.32479/ijeep.11228